Islamic Journalists in Socializing the Values of Religious Moderation - M. Yoserizal Saragih (Budapest International Research and Critics University, 2021)
This paper discusses Islamic journalism in disseminating the values of religious moderation. The purpose of this paper is to increase knowledge and increase understanding of the importance of religious moderation values in maintaining national unity and integrity. This paper is a descriptive analysis that aims to describe, describe, inventory, and analyze the conditions being investigated in a systematic, factual and accurate manner, then from the results of the analysis a conclusion can be drawn. The results of the analysis of the discussion show that Islamic journalism is a profession in the field of conveying or disseminating information to listeners, viewers or readers that contains Islamic values. Islamic journalism is also known as a journalist who contains good values based on the Qur'an and hadith. Meanwhile, religious moderation; perspective in acting, responding, respecting, appreciating various differences in religious diversity, differences in race, ethnicity, culture, customs, and also ethics in order to maintain the unity of the religious community and maintain the unity of a peaceful and prosperous nation. In disseminating the values of Islamic journalism, Islamic journalism applies the principles of justice, balance, kindness, wisdom, istiqamah, and tolerance. By carrying out their functions as muaddib (educators), musaddid (information straighteners), mujaddid (reformers), muwahid (unifiers), and fighters (mujahid). Islamic journalism realizes the values of religious moderation by spreading Islamic teachings such as aqidah, worship, morals (exemplary), sharia, and muamalah.